The Impact Of Business Relocation On The Socio Economic Conditions Of Chili Traders At Mardika Market - Angely Paley; Martha Turukay; Maise T. F Tuhumury (International Journal of Business and Quality Research, 2026)
Abstract Market relocation constitutes a policy instrument employed by local governments to support urban spatial planning and enhance the quality of commercial infrastructure. However, its implementation often generates multidimensional consequences, particularly for the socio-economic conditions of actors operating within the informal sector. This study aims to examine the impact of business relocation on the socio-economic conditions of chili traders at Mardika Market, Ambon City. The research adopted a quantitative approach using a survey method conducted in December 2025. The study involved 30 respondents selected through purposive sampling, consisting of chili traders who had experienced relocation and remained actively engaged in trading activities. Data were collected through observation, interviews, and structured questionnaires, and subsequently analyzed using descriptive statistics and the Wilcoxon Signed Rank Test to assess differences in conditions before and after relocation.The findings reveal that business relocation exerted a significant influence on the traders' social conditions, as reflected in changes in social interactions, perceived security, and environmental cleanliness. Furthermore, relocation also affected the economic dimension, particularly through alterations in working hours and a decline in traders’ income levels. These findings suggest that although market relocation has the potential to improve the physical quality of market facilities, the policy has not yet fully ensured the economic sustainability of traders’ livelihoods. Therefore, more adaptive and welfare-oriented policy interventions are required to better accommodate the needs and long-term economic resilience of informal business actors.